Altered Spontaneous Brain Activity Patterns and Functional Connectivity in Adults With Intermittent Exotropia: A Resting-State fMRI Study - He, Xueying; Hong, Jie; Wang, Qian; Guo, Yanan; Li, Ting; Qu, Xiaoxia; Liu, Jing; Li, Wei; Zhang, Lirong; Fu, Jing; Liu, Zhaohui (Frontiers in Neuroscience, 2021)
The purpose of this study is to investigate brain functional changes in patients with intermittent exotropia (IXT) by analyzing the amplitude of low-frequency fluctuation (ALFF) of brain activity and functional connectivity (FC) using resting-state functional magnetic resonance imaging (rs-fMRI). Twenty-six IXT patients and 22 age-, sex-, education- and handedness-matched healthy controls (HCs) were enrolled and underwent rs-fMRI. The ALFF, fractional ALFF (fALFF) values in the slow 4 and slow 5 bands, and FC values were calculated and compared. The correlations between ALFF/fALFF values in discrepant brain regions and clinical features were evaluated. Compared with HCs, ALFF/fALFF values were significantly increased in the right angular gyrus (ANG), supramarginal gyrus (SMG), inferior parietal lobule (IPL), precentral gyrus (PreCG) and the bilateral inferior frontal gyri (IFG), and decreased in the right precuneus gyrus (PCUN), left middle occipital gyrus (MOG) and postcentral gyrus (PoCG) in IXT patients. The Newcastle Control Test score was negatively correlated with ALFF values in the right IFG (r = -0.738, p <0.001). The duration of IXT was negatively correlated with ALFF values in the right ANG (r = -0.457, p =0.049). Widespread increases in FC were observed between brain regions, mainly including the right cuneus (CUN), left superior parietal lobule (SPL), right rolandic operculum (ROL), left middle temporal gyrus (MTG), left IFG, left median cingulate gyrus (DCG), left PoCG, right PreCG and left paracentral gyrus (PCL) in patients with IXT. No decreased FC was observed. Patients with IXT exhibited aberrant intrinsic brain activities and FC in vision- and eye movement-related brain regions, which extend current understanding of the neuropathological mechanisms underlying visual and oculomotor impairments in IXT patients.